Оптимальні пластинчасті теплообмінники енергетичних установок - Алтухова, Ольга Василівна; Канівець, Георгій Євдокимович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Пластинчасті теплообмінники є ефективним видом теплообмінного обладнання та можуть використовуватись у багатьох енергетичних установках. У статті аналізується їх використання у якості маслоохолоджувачів та підігрівачів води паротурбінних установок, підігрівачів повітря системи знеліднення газотурбінних установок, регенераторів понадкритичних СО2 циклів. Наведено оптимальні типорозміри теплообмінників та швидкості середовищ для ряду навантажень, дано рекомендації щодо застосування теплообмінників у залежності від параметрів та конфігурації циклів.

Plate heat exchangers are an effective type of heat exchange equipment and can be used in many power plants. The article analyzes the use of corrugated plate heat exchangers in a number of installations. Their optimization was done according to the economic criterion of optimality, taking into account capital investments and operating costs. The analysis of the plate heat exchangers uses as oil coolers (a number of loads with oil mass flow rates 10….250 kg/s) and water heaters (heat power 100…2000 kW) of steam turbine plants. It has been established that plate oil coolers are more economical than shell-and-tube ones. Also, the anti-icing system plate air heaters of gas turbine plants with a power of 1 to 20 MW considered. The air for the anti-icing system was taken after the compressor and was additionally heated by exhaust gases. It has been established that it is necessary to install an additional flue gas smoke exhauster for using plate heat exchangers. Air must be extracted after the compressor, otherwise, low air density leads to high hydraulic losses, which makes it impossible to use plate heaters. Optimum air velocities are in the range of 0.4…0.6 m/s, flue gas velocities are 4…6 m/s. The use of standard plate heat exchangers with corrugated plates is impractical for GTU powers above 5 MW. Optimization of plate regenerators of supercritical CO2 cycles with recompression for powers from 1 to 15 MW has been done. Optimum velocities of hot CO2 are about 0.8 m/s, cold ones 0.3…0.5 m/s. The optimal sizes of plate heat exchangers are recommended for all of the above applications.
Optimal plate heat exchangers of power generation systems
Keywords: паротурбінний цикл; газотурбінний цикл; система знеліднення; понадкритичний СО2 цикл; steam turbine cycle; gas turbine cycle; anti-icing system; supercritical CO2 cycle with recompression